A253 ADMINISTRATIVE DATA CAN ACCURATELY IDENTIFY PATIENTS WITH PERIANAL CROHN’S DISEASE - Fairclough, J (J Can Assoc Gastroenterol, 2020)
BACKGROUND: Perianal fistulas (PAF) are a frequent complication of Crohn’s disease (CD) associated with substantial morbidity. Population-based studies with CD are lacking, in part due to the difficulty in identifying these patients from health administrative databases. AIMS: To determine if administrative claims and diagnostic codes can reliably identify patients with perianal fistulas in a cohort of patients with CD. METHODS: A retrospective cohort study was performed using data from The Ottawa Hospital (TOH), which was linked to The Institute for Clinical Evaluative Sciences (ICES) Ontario Crohn’s and Colitis Cohort (OCCC) data using Ontario Health Insurance Plan (OHIP) numbers. Patients admitted with CD from 1 Jan 2009 to 31 Dec 2016 were identified from TOH data warehouse using the ICD-10 code K50.x. Confirmation of CD diagnosis and determination of the presence or absence of PAF was achieved by a longitudinal, manual chart review. Patients with and without PAF were abstracted in a 1:2 ratio to serve as a reference gold standard for PAF status. ICES captures all publicly reimbursed diagnostic tests, interventional procedures and physician billing codes, including MRI pelvis utilization and surgical procedures associated with perianal fistulas in Ontario. Sixteen case definitions for PAF in ICES were specified a priori. Two by two contingency tables were constructed to assess the sensitivity, specificity, positive predictive value (PPV) and negative predicative value (NPV) of each case definition against the gold standard PAF status as determined by TOH data. Youden’s index and Kappa were used to select a case definition that best identified TOH PAF patients. Results: A total of 136 patients with active PAF and 351 without PAF were included in the linked analysis. There were a similar proportion of male patients with and without PAF (49% vs. 43%). Patients with PAF were slightly younger; 69% were aged 18–44 compared to 58% of patients without PAF. Sensitivity of the case definitions ranged from 0.44 to 0.98, and specificity from 0.45 to 1.00. A case definition that combined at least two of fistula diagnosis code, perianal surgical procedures associated with fistulas, and radiologic imaging codes of the pelvis, all within 2 years, had the best performance using Youden’s index and Kappa. It discriminated between patients with or without PAF with sensitivity of 0.80 and specificity of 0.92. CONCLUSIONS: Using a cohort of CD patients from a single tertiary care center we derived a case definition that could accurately distinguish CD patients with and without PAF in a provincial health administrative database. Once validated this will allow for future population-based studies to assess trends in PAF. FUNDING AGENCIES: Takeda Pharmaceuticals